Two-step fabrication of single-layer rectangular SnSe flakes. (19th April 2017) - Jiang, Jizhou; Wong, Calvin Pei Yu; Zou, Jing; Li, Shisheng; Wang, Qixing; Chen, Jianyi; Qi, Dianyu; Wang, Hongyu; Eda, Goki; Chua, Daniel H C; Shi, Yumeng; Zhang, Wenjing; et al.
Abstract: Recent findings about ultrahigh thermoelectric performances in SnSe single crystals have stimulated research on this binary semiconductor material. Furthermore, single-layer SnSe is an interesting analogue of phosphorene, with potential applications in two-dimensional (2D) nanoelectronics. Although significant advances in the synthesis of SnSe nanocrystals have been made, fabrication of well-defined large-sized single-layer SnSe flakes in a facile way still remains a challenge. The growth of single-layer rectangular SnSe flakes with a thickness of 6.8 Å and lateral dimensions of about 30 µ m × 50 µ m is demonstrated by a two-step synthesis method, where bulk rectangular SnSe flakes were synthesized first by a vapor transport deposition method followed by a nitrogen etching technique to fabricate single-layer rectangular SnSe flakes in an atmospheric pressure system. The as-obtained rectangular SnSe flakes exhibited a pure crystalline phase oriented along the a -axis direction. Field-effect transistor devices fabricated on individual single-layer rectangular SnSe flakes using gold electrodes exhibited p -doped ambipolar behavior and a hole mobility of about 0.16 cm 2 V −1 s −1 . This two-step fabrication method can be helpful for growing other similar 2D large-sized single-layer materials.